Fully percutaneous insertion and removal of the Impella CP via a subclavian approach - Sacha, Jerzy; Krawczyk, Krzysztof; Gierlotka, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
The Impella (Abiomed) is a mechanical circulatory support device which augments cardiac output, but may also unload a left ventricle during venoarterial extracorporeal membrane oxygenation (ECMO) [1]. However, the Impella requires an access to a large artery and this may be problematic in a severe peripheral arterial disease. The presented case demonstrates how to insert and remove the Impella CP via a subclavian approach without surgical cutting.